A case series of paediatric patients with spinal muscular atrophy type I undergoing scoliosis correction surgery. Issue 2 (17th November 2021) - Kong Kam Wa, T.; Holmes, C.; O'Brien, K.
Summary: Spinal muscular atrophy is a neuromuscular disorder with degeneration of spinal motor neurons. Type I is a severe variant that was recently shown to be amenable to treatment with the antisense oligonucleotide nusinersen. As a result of increased life expectancy with this treatment, more children with spinal muscular atrophy type I are presenting for spinal correction surgery. In this case series, we present four such patients who underwent spinal surgery at our institution over the course of one year. Pre‐operative assessment showed evidence of reduced respiratory function requiring nocturnal non‐invasive ventilation in all four patients. A difficult airway was encountered in two of the four patients. Postoperative complications were ubiquitous and included CSF leak, poor wound healing, metal frame exposure, frame instability and wound infection. There were no postoperative respiratory complications and all four children returned to their respiratory baseline postoperatively. All patients underwent successful lumbar puncture and intrathecal nusinersen injection following their spinal surgeries. Given the risk of complications and prolonged recovery following spinal surgery, a detailed family discussion is advisable.